Biological Activity of Thiazole Derivatives on Some Pathogenic Microorganisms - Hassan, Firas A; Saeed, Zahraa S; Ahmad, Shayma M (Al-Nahrain Journal of Science, 2018)
The thiazole derivatives were prepared by the reaction of benzaldehyde derivatives with (2-thiooxamide-5-(p-bromobenzene)-1,3-thiazole) that was readily prepared by heating dithiooxamide with 4-bromophenacylbromide. Within invitro study the the effect of the prepared compounds on the growth of two types of fungi geotrichum cadidum and Trichophyton rubrum and the bacteria Escherichia coli, pseudomonas aeruginosa, Staphylococcus aureus, and Klebsiella pneumoniae was evaluated. Incubation time and concentration were studied to find the optimal conditions for the activity. Compound II with the concentration 20 mg/ml found to be the most active compound toward geotrichum and Trichophyton rubrum. Statistical analysis of the values of colonial diameter shows low percentage error for the studied fungi with regard to incubation time.